2016
DOI: 10.1097/mcp.0000000000000322
|View full text |Cite
|
Sign up to set email alerts
|

Eye disorders associated with obstructive sleep apnoea

Abstract: This review highlights the need for ophthalmologists to consider OSA in their patients and also makes recommendations for future research studies, especially whether therapies for OSA can be effective for ocular disorders also.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
(18 reference statements)
0
10
0
1
Order By: Relevance
“…It is known that these are core mechanisms involved in the pathogenesis of cardiovascular disease (CVD), diabetes and other neurological disorders [8]. Although OSA is a well-known major risk factor for many systemic diseases and multi-organ dysfunction [9], a few studies have additionally reported that OSA is associated with eye disorders [10-12]. These studies suggested that the main mechanisms leading to the ocular complications of OSA are mainly intermittent hypoxia, sympathetic overstimulation, oxidative stress, and damaging effects of endothelin-1 (ET-1) [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that these are core mechanisms involved in the pathogenesis of cardiovascular disease (CVD), diabetes and other neurological disorders [8]. Although OSA is a well-known major risk factor for many systemic diseases and multi-organ dysfunction [9], a few studies have additionally reported that OSA is associated with eye disorders [10-12]. These studies suggested that the main mechanisms leading to the ocular complications of OSA are mainly intermittent hypoxia, sympathetic overstimulation, oxidative stress, and damaging effects of endothelin-1 (ET-1) [13].…”
Section: Introductionmentioning
confidence: 99%
“…FES is a condition characterized by easily rotating and drooping lids, papillary conjunctivitis, and corneal epithelial erosions (11). The prevalence of FES in the general population ranges from 2.3% to 3.8% (12).…”
Section: Discussionmentioning
confidence: 99%
“…The reported frequency of unilateral KC using computerized videokeratography techniques ranges between 0.5 and 4% [2]. Different studies [15][16][17][18][19] have shown that KC patients display a higher prevalence of obstructive sleep apnea compared with the general population. Another study has shown an association between floppy eyelid syndrome and KC [20]; it seems to be a cause of corneal collagen crosslinking failure [21].…”
Section: Introductionmentioning
confidence: 99%